Влияние содержания карбонильного железа на свойства модифицированной связки Fe-Ni-Cu-Sn, используемой при изготовлении алмазных кругов для резки строительных материалов и дорожных покрытий - Ильющенко, А.Ф.; Баран, А.А.; Побережный, С.В.; Звонарев, Е.В. (Породоразрушающий и металлообрабатывающий инструмент – техника и технология его изготовления и применения, 2010)
The results and findings relating to the appropriate influence of fine disperse carbonyl iron
powder on physical and mechanical features of Fe-Ni-Cu-Sn bonding composition for diamond tool
are covered as well as these ones regarding the influence of wear resistant fillers and additional
abrasives which are incorporated into matrix bonding material. The influence concerns the abovementioned
features. The operation cutting diamond tool parameters for a number of promising
bonding systems are presented.